Investigating student’s attitude towards waste management: A study among Inasis Bank Rakyat’s resident - Teoh, Shi Yun; Ibrahim, Jafni Azhan (Universiti Utara Malaysia, 2020)
This paper explores the relationship between students’ attitudes towards waste management in Inasis Bank Rakyat. The factors were investigated within the framework which are awareness, disposition method and risk perception of waste management. As Inasis Bank Rakyat population increase, the amount of waste also increases. Quantitative research methods were carried out in Inasis Bank Rakyat and 104 students were the sample. The Data collected by the questionnaire. In the study, females had a more positive attitude towards waste management than males. The respondents have poor awareness of proper waste management as well as showing a low disposition method of waste management has resulted in the generation of large amounts of waste in the Inasis Bank Rakyat. Therefore, the attitude of students is necessary for better waste management in order to create a healthy environment.